46, XXovotesticular disorder of sex development with serous cystadenomas of the ovary - Fernandes Gwendolyn; Shital Munde; Pranav Pramod Patwardhan; Leena Naik (International Journal of Medical Research and Review, 2017)
Ovotesticular disorder of sex development (DSD) is an extremely rare condition and is defined as presence of both ovarian and testicular tissue in the same individual, regardless of the karyotype and the status of the external or internal genitalia. This disorder was formerly called True hermaphroditism and 400-500 cases have been reported in literature till date. Various chromosomal abnormalities have been described but 46XX is the commonest. Both Mullerian and Wolffian duct derivatives are present in the same individual and the external as well as internal genitalia display a spectrum of phenotypes. The external genitalia are ambiguous and a uterus and a phallus areoften present. The gonads may be ovotestis or a combination of ovary on one side and testes or ovotestis on the other side. These gonads are prone to develop both benign and malignant neoplasms. Tumors like dysgerminoms, seminomas, gonadoblastoma, and mucinous cystadenomas have been described. Serous cystadenomas however, have not been described.